The muslim heritage of Bengal : the lives, thoughts and achievements of great muslim scholars, writers and reformers of Bangladesh and West Bengal - Khan, Muhammad Mojlum (Kube Publishing, 2013)
The Muslim Heritage of Bengal is a multidimensional work. . . . I am sure this book will add to the vista of knowledge in the field of Muslim history and heritage of Bengal. I recommend this work.""?Dr A. K. M. Yaqub Ali, Professor Emeritus, Islamic History et Culture, University of Rajshahi ""Khan's book provides invaluable information which will inspire present and future generations.""?Dr M. Abdul Jabbar Beg, former professor of Islamic History and Civilization, National University of Malaysia A popular history that covers eight hundred years of the history of Islam in Bengal through th.